(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study aims to design and implement a web-based employee attendance information system using the Laravel framework at PT Hesed Indonesia, with the main contribution being the integration of real-time attendance data management features, automatic reports, and centralized access rights settings that were not available in the previous system. This system was developed to replace the manual attendance method, which was prone to recording errors, data manipulation, and slowed down the reporting process. Development was carried out using the Waterfall method, which includes the stages of requirement definition, design, coding & testing, integration & system testing, and operation & maintenance. A trial was conducted on 25 employees over one month, resulting in an attendance recording accuracy rate of 98% and a 70% reduction in recapitulation time compared to the previous method. The implementation results show that the system can improve efficiency and ease of data access, although it still has limitations such as the lack of integration with fingerprint devices or payroll systems. In the future, this system can be developed with attendance notification features, IoT integration for automatic attendance, and attendance data analysis to support managerial decisions.